Minor Histocompatibility Antigen UTY as Target for Graft‐versus‐Leukemia and Graft‐versus‐Haematopoiesis in the Canine Model. (26th December 2012) - Bund, D.; Buhmann, R.; Gökmen, F.; Zorn, J.; Kolb, H.‐J.; Schmetzer, H. M.
Abstract Male patients with female‐stem‐cell donors have better prognosis compared to female‐to‐male combinations due to Y‐encoded minor histocompatibility antigens recognized by female‐alloimmune‐effector lymphocytes in the context of a graft‐versus‐leukemia (GvL) effect. We provide data in a dog‐model that the minor histocompatibility antigen UTY might be a promising target to further improve GvL‐immune reactions after allogeneic‐stem‐cell transplantations. Female‐canine‐UTY‐specific T cells (CTLs) were stimulated in vitro using autologous‐DCs loaded with three HLA‐A2‐restricted‐UTY‐derived peptides (3‐fold‐expansion), and specific T cell responses were determined in 3/6 female dogs. CTLs specifically recognized/lysed autologous‐female‐peptide‐loaded DCs, but not naïve‐autologous‐female DCs and monocytes. They mainly recognized bone‐marrow (BM) and to a lower extent DCs, monocytes, PBMCs and B‐cells from DLA‐identical‐male littermates and peptide‐loaded T2‐cells in an MHC‐I‐restricted manner. A UTY‐/male‐specific reactivity was also obtained in vivo after stimulation of a female dog with DLA‐identical‐male PBMCs. In summary, we demonstrated natural UTY processing and presentation in dogs. We showed that female‐dog CTLs were specifically stimulated by HLA‐A2‐restricted‐UTY peptides, thereby enabling recognition of DLA‐identical‐male cells, mainly BM cells. These observations suggest UTY as a promising candidate‐antigen to improve GvL‐reactions in the course of immunotherapy.